The embryology of Prionium serratum (L.f.) Drege ex E.Mey. (Juncaceae:Cyperales) and its implications for the phylogeny of Cyperales - Munro, Sioban Lucille (Department of Biological Sciences, 2023)
This study investigates the phylogenetic placement of Prionium serratum, a monotypic genus in the family Juncaceae and the consequences of this on the evolutionary relationships of Cyperales using embryology, morphology and rbcL sequence data. The embryology of Prionium conforms to that found in Juncaceae. The tapetum is glandular-secretory and microsporogenesis is simultaneous. Pollen is united in tetrahedral and cross tetrads and is tri-nucleate at release. The ovary is trilocular, there are three stigmata and the style is absent. There are many ovules per locule and placentation is axile. The ovule is anatropous, bitegmic and crassinucellate. The embryo sac conforms to the Polygonum type of development. Endosperm formation is helobial and embryogeny is of the Onagrad type, Juncus variation. The mature embryo is linear in shape and is embedded within the endosperm. The seed is trigonal, lacks processes and the seed coat is formed from both integuments. Germination is epigeal and the seedlings are of Type A. Phylogenetic analyses using morphological data (including embryology) and total evidence (rbcL sequence data combined with morphological data) revealed that Juncaceae are paraphyletic with Prionium basal to Juncaceae plus Cyperaceae within Cyperales in both instances. In addition, Oxychlae is basal to Cyperaceae in the total evidence analysis. The basal placement of Prianium within Cyperales is supported by its woody habit, carpels fused in the ovary region chlorenchymatous air canals in the leaf and the absence of air canals between vascular bundles. The total evidence phylogeny is in agreement with Plunkett et al.'s (1995) rbcL topology and this study also supports Cutler's (1969) contention that Prianium should be excluded from Juncaceae. Therefore, it is suggested that Prianium be elevated to family status.